Experiences of Tibetan Refugees in India during the COVID-19 Pandemic - Tso, Lhamo; Shukla, Meenakshi (Refuge, 2022)
This study explores the experiences of 70 Tibetan refugees in India (28 male, 42 female; mean age = 30.90 years; SD = 8.11) during the COVID-19 pandemic in terms of their stress, financial anxiety, perceived discrimination, dark future expectations, and resilience. Older, married, and working refugees experienced more problems but higher resilience. Female refugees reported more nervousness and stress than male refugees. Financial anxiety and dark future expectations predicted higher stress. Overall, the findings show low to moderate levels of mental health issues and high resilience among Tibetan refugees during the pandemic and highlight the importance of cultural beliefs and practices in maintaining good mental health and resilience.